NEOINDUSTRIALIZATION OF THE AGRICULTURAL SECTOR OF THE ECONOMY AS A NECESSARY CONDITION FOR INNOVATIVE TRANSFORMATION OF PRODUCTIVE FORCES AND ACHIEVING TECHNOLOGICAL SOVEREIGNTY - Ivan SANDU; Vasily NECHAEV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article is devoted to the problem of ensuring technological sovereignty in the agrarian sector of the Russian economy, its neoindustrialization. The purpose of the work is a scientific and theoretical substantiation of the possibilities of innovative and investment development of the agro-industrial complex in the context of modern trends in neoindustrialization. Empirically, the assessment of the scale of neoindustrialization in the agricultural sector was carried out, a conclusion was made about its initial stage, characterized by a lag in the technological development of agriculture from other sectors of the economy, insufficient use of the results of intellectual activity, and a lower scale of innovative products. A mathematical model of a two-factor regression is constructed that characterizes the process of neoindustrialization in agriculture in Russia, and a predictive assessment of the dynamics of indicators of neoindustrialization of agriculture based on trend analysis is presented. The calculations show that with an increase in the level of labor productivity by 1%, the share of innovative products in the shipped agricultural products will increase by 0.23 percent. The necessity of improving the organizational and economic mechanism for implementing the strategies of innovative and scientific and technological development in order to increase the innovative activity of enterprises in the agricultural sector is substantiated. The practical significance of the results of the study is to develop measures to improve innovation and science and technology policy in order to achieve positive effects from neo-industrialization in the agricultural sector during the transition to Industry 4.0.